Towards a Palliative Culture: Level of Knowledge and Misconceptions about Palliative Care, Palliative Sedation, and Euthanasia (Revista Iberoamericana de Bioética, 2024)
The objective of this study was to analyze the level of knowledge of the concepts of palliative care, palliative sedation and euthanasia that could influence ethical decision-making related to the end of life. Accordingly, an ad hoc questionnaire was drawn up and given to those attending Palliative Care Conferences in the Community of Madrid (n = 142). Student's T showed that there are significant differences (p < 0.05) between the three pairs of concepts, and correlations were found between the degree of knowledge of the three constructs. Work experience and level of knowledge in palliative care correlates with greater knowledge of euthanasia and palliative sedation, finding statistically significant differences according to level of education. These results suggest that promoting knowledge of palliative care will reduce the presence of erroneous ideas in deliberations related to the end of life, sedation and euthanasia.
Keywords: palliative care; palliative sedation; bioethical issues; euthanasia; end of life; public health